Longitudinal study on nerve ultrasound and corneal confocal microscopy in NF155 paranodopathy. Issue 6 (20th May 2020) - Athanasopoulos, Diamantis; Motte, Jeremias; Fisse, Anna Lena; Grueter, Thomas; Trampe, Nadine; Sturm, Dietrich; Tegenthoff, Martin; Sgodzai, Melissa; Klimas, Rafael; Querol, Luis; Gold, Ralf; Pitarokoili, Kalliopi
Abstract: We report the case of a 27‐year‐old patient with subacute anti‐neurofascin‐155 neuropathy with bifacial palsy, who showed excellent response to rituximab. We provide longitudinal data of established clinical scores, nerve conduction studies, antibody titers, and novel imaging methods (nerve ultrasonography and corneal confocal microscopy). Clinical and electrophysiological improvement followed the reduction of serum antibody titer and correlated with a reduction of corneal inflammatory cellular infiltrates whereas the increase in the cross‐sectional area of the peripheral nerves remained 12 months after first manifestation. Our findings suggest that novel techniques provide useful follow‐up parameters in paranodopathies.